Tuḥfat Sarandib Tadhkirat li al-Muḥib Karya Al-Raniri: Pemikiran Teologis Ulama Melayu di Tanah Saylan - Sulaiman Ibrahim (Manuskripta, 2015)
This article is about manuscript of Tuḥfat Sarandib Tadhkirat li al-Muḥib created by Al-Raniri. This is manuscript of Martabat Tujuh (The Dignity of the Seven) which discuss about nature in relation of man and God and how human beings should be at peace with nature. This article will reveals the background of Al-Raniri as a litterateur, his works and his Islamic orientations. Moreover, this paper explains about the manuscript Tuḥfat Sarandib Tadhkirat li al-Muḥib, associated with the Malays and the land of Sarandib/Saylan (Srilanka) as well as the relationship between manuscript interpreter and the location where the manuscript was translated. In addition of that, this article also discusses the steps of philological research, i.e. inventory, description, comparison of texts, extracts of the text. This article concludes with text translation of Tuḥfat Sarandib Tadhkirat li al-Muḥib for easier understanding for the reader. --- Artikel ini membicarakan naskah Tuḥfat Sarandib Tadhkirat li al-Muḥib karya Al-Raniri. Naskah ini merupakan naskah Martabat Tujuh yang membahas perihal alam dalam hubungannya dengan manusia dan Tuhan serta bagaimana manusia harus berdamai dengan alam. Artikel ini akan mengungkap latar belakang Al-Raniri sebagai penulis naskah berikut karya-karya dan orientasi keislamannya. Selain itu, di dalam tulisan ini dibahas tentang naskah Tuḥfat Sarandib Tadhkirat li al-Muḥib yang berhubungan dengan Melayu dan Negeri Sarandib/Saylan (Srilanka) serta hubungan antara penerjemah naskah dan daerah tempat naskah ini diterjemahkan. Selain membahas masalah di atas, artikel ini juga membahas langkah-langkah penelitian filologi, yaitu inventarisasi, deskripsi, perbandingan teks, suntingan teks. artikel ini ditutup dengan disajikannya terjemahan teks Tuḥfat Sarandib Tadhkirat li al-Muḥib agar teks ini dapat mudah dipahami oleh pembaca.